2016
DOI: 10.1159/000450674
|View full text |Cite
|
Sign up to set email alerts
|

Reference Ranges of Reticulocyte Haemoglobin Content in Preterm and Term Infants: A Retrospective Analysis

Abstract: Background: Despite iron supplementation, some preterm infants develop iron deficiency (ID). The optimal iron status parameter for early detection of ID has yet to be determined. Objective: To establish reference ranges for reticulocyte haemoglobin content (Ret-He) in preterm and term infants and to identify confounding factors. Methods: Retrospective analyses of Ret-He and complete blood count in infants with a clinically indicated blood sample obtained within 24 h after birth. Results: Mean (SD) Ret-He was 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 24 publications
(41 reference statements)
0
22
0
Order By: Relevance
“…For all infants with a Ret-H e value below the reference range of <25 pg [3], we checked if the MCV values were within the GA-specific reference ranges [2]. Out of 10 infants with a Ret-H e of <25 pg, 8 had MCV values within the reference range, 1 had an MCV value below the reference range, and 1 had an MCV value above the reference range.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For all infants with a Ret-H e value below the reference range of <25 pg [3], we checked if the MCV values were within the GA-specific reference ranges [2]. Out of 10 infants with a Ret-H e of <25 pg, 8 had MCV values within the reference range, 1 had an MCV value below the reference range, and 1 had an MCV value above the reference range.…”
Section: Resultsmentioning
confidence: 99%
“…However, the postnatal changes in Ret-H e , which are more pronounced in preterm than in term infants, need to be taken into account when using Ret-H e as an iron status parameter within the first days after birth. The reference range (2.5th and 97.5th percentile) for Ret-H e in term and preterm infants within 24 h of birth is 25-37 pg [3]. The postnatal decline in Ret-H e observed in this study population was substantial, but future studies are needed to answer the question whether this finding is actually of clinical relevance and should therefore influence treatment decisions.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…14 Yet, GA has a negligible impact on RET-He levels. 15 Platelet counts mildly increase with GA and the IPF decreases. [16][17][18] Reviewing the work of Mouzinho et al 19 and Manroe et al 20 with healthy newborns revealed that neutrophil counts in low-birthweight preterm newborns weighing less than 1500 g were lower and had a wider range of distribution than in larger, term newborns.…”
Section: Discussion Factors That Can Affect Cbc Reference Intervalsmentioning
confidence: 95%